ADORABLE PROJECTS’ DIGITAL MARKETING APPROACHES IN COMPETITIVE FASHION INDUSTRY - Ayunda, Kirana Sekar (Jurnal Ilmiah Ilmu Komunikasi Communique, 2025)
Companies are compelled by the digital age's competitive phenomenon to not only develop innovative products but also to enhance customer loyalty and fortify their emotional bonds with them. In order to preserve and improve client relationships, Adorable Projects, a local fashion brand in Indonesia, uses digital marketing techniques. This study intends to examine these tactics. Data was gathered using semi-structured interviews, observations, and literature reviews as part of a descriptive qualitative methodology. According to the results, Adorable Projects makes good use of digital marketing techniques like social media, e-commerce, and themed material. The implementation of Integrated Marketing Communication (IMC) also contributes to the development of a unified brand experience across platforms. The brand's competitive position in the local market is strengthened by these strategies, which also improve customer engagement. Furthermore, the implementation of Integrated Marketing Communication (IMC) ensures a consistent brand experience across numerous platforms, reinforcing the company's identity and values. Key techniques include using visually appealing material customized to certain audiences, utilizing live-streaming features on e-commerce platforms for real-time interaction, and exploiting platform-specific features to improve customer accessibility and trust. The findings of this study are a great resource for businesses in similar industries trying to improve their digital marketing and IMC strategies. This study emphasizes the need of connecting campaigns with customer patterns and preferences in order to achieve long-term success in the competitive fashion business.